Editorial 10.3 - Harvey, Marina; Luzia, Karina (Journal of University Teaching and Learning Practice, 2013)
This marks my final issue as Senior Editor of JUTLP and I would like to congratulate the new senior editorial team: Romy Lawson, Alisa Percy and Dominique Parrish. I know I leave the journal in very good hands and the leadership team will ensure that JUTLP will continue to champion teaching and learning in higher education. I would like to also thank all the people who have contributed to the success of this journal: the authors, the reviewers, the members of the editorial board, and those who have contributed to the editing and desktop publishing processes. I would also like to thank you , the reader – without you there is no purpose for our writing. I feel very privileged to introduce the editorial for this special issue of JUTLP as improving opportunities for sessional staff has been a passion throughout my academic career. I would particularly like to thank all who have contributed to the reviewing for this edition and wish to congratulate Marina and Karina for their hard work in producing this edition and in exciting outcomes from the Benchmarking leadership and advancement of standards for sessional teaching project. Geraldine Lefoe, Senior Editor Editorial Marina Harvey & Karina Luzia How do you measure up? Standards for sessional staff teaching: moving from periphery to core. Sess•ion•al Staff /sessional stǽf/ noun. Any teachers in higher education employed on a casual or contract or sessional basis. This includes lecturers, tutors, online course facilitators and moderators, markers and demonstrators. [BLASST.edu.au] Sessional staff provide the majority of teaching in Australian universities (May, Strachan, Broadbent & Peetz 2011; Percy et al. 2008). They are important, yet have been on the ‘periphery’ (Kimber 2003) of learning and teaching plans. The time has come to ensure that sessional staff are now acknowledged and actively included as ‘core’ to quality learning and teaching. This special issue of the Journal of University Teaching and Learning Practice is an outcome of the national BLASST (Benchmarking leadership and advancement of standards for sessional teaching) project. A key motivator for the project was to systematise good practice through the establishment of a national standards framework. The result is the BLASST framework which is underpinned by three key principles: quality learning and teaching, support for sessional staff and sustainability. This framework is a truly collaborative product: the result of years of research and commitment by a large number of people who shared a vision for quality learning and teaching with sessional staff. In the true sense of distributed leadership, these people included academics, professional staff, sessional staff and students from all levels and disciplines of several universities. Their engagement and research generated new insights, learning and knowledge about sessional staff.